Unleashing entrepreneurial potential in transition economies: A comparative analysis of the impact of macro and micro policies - Fadil Sahiti (European Journal of Government and Economics (EJGE), 2023)
This study investigates the relationship between macroeconomic and microeconomic policies and entrepreneurial dynamics in two economies transitioning from planned economies to free markets, comparing them to a developed economy. Macroeconomic policies, despite not directly targeting entrepreneurship, significantly impact entrepreneurial dynamics. Conversely, microeconomic policies specifically aim to promote and enhance entrepreneurial activity. The analysis links policy quality to key entrepreneurial indicators: new firm creation, incumbent firm survival, and overall firm stock. Findings reveal that while transition economies often adopt entrepreneurship policies similar to developed nations, some remain country-specific. These policy variations manifest in distinct entrepreneurial dynamics across the economies.
Keywords: L53; P20; O57; L26; 330; entrepreneurship policy; start-up; transition economies